Juridical Analysis of the Judge's Decision on the Case of Planned Murder Committed by a Child (Case study of decision 5/Pid.Sus-anak/2023/PN.Mks) - Erfinda Septiana (Proceedings Series on Social Sciences & Humanities, 2023)
Premeditated murder is the crime of taking the life of another human being, or killing, after planning the time or method, with the aim of ensuring the success of the murder or to avoid arrest. Many cases of premeditated murder which are prohibited acts and regulated in the Criminal Code contained in Article 340, however, this is certainly different if the murder is committed by a child who uses Law Number 35 of 2014 concerning Child Protection. Based on this, the researcher is interested in further examining whether the sanctions given have been justified and are in accordance with the applicable law. This article is prepared to examine and determine the suitability of the application of sanctions for premeditated murder committed by children in review of Decision Number 5/Pid.Sus-anak/2023/PN.Mks. In addition, this article also aims to find out the judge's consideration in imposing sanctions or punishment on the perpetrator. The writing of this article uses normative legal research methods based on the study of laws to answer the legal problems at hand. Based on this research, it is reviewed from the decision Number 5/Pid. Sus-anak/2023/PN. Mks. Then the perpetrator was sentenced to 10 (ten) years imprisonment. Based on Article 80 Paragraph (3) of Law of the Republic of Indonesia Number 35 of 2014 amending Law Number 23 of 2002 concerning Child Protection which explains that every person who commits violence against a child causing death is punishable with a maximum imprisonment of 5 (five) years.